2014
DOI: 10.1186/1423-0127-21-6
|View full text |Cite
|
Sign up to set email alerts
|

A new pharmacological role for donepezil: attenuation of morphine-induced tolerance and apoptosis in rat central nervous system

Abstract: BackgroundTolerance to the analgesic effect of opioids is a pharmacological phenomenon that occurs after their prolonged administration. It has been shown that morphine-induced tolerance is associated with apoptosis in the central nervous system and neuroprotective agents which prevented apoptosis signaling could attenuate tolerance to the analgesic effects. On the other hand donepezil, an acetylcholinesterase inhibitor, has been reported to have neuroprotective effects. Therefore in this study, the effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…Regarding effects on analgesia, both donepezil or rivastigmine increased morphine’s acute analgesic effects [138]. Donepezil, rivastigmine and scopolamine each attenuated the development of tolerance to morphine’s analgesic effects [134, 138, 139]. In contrast, mecamylamine did not affect tolerance to morphine’s analgesic effects [126].…”
Section: Ach As Treatment Target For Oud: Current Evidencementioning
confidence: 99%
“…Regarding effects on analgesia, both donepezil or rivastigmine increased morphine’s acute analgesic effects [138]. Donepezil, rivastigmine and scopolamine each attenuated the development of tolerance to morphine’s analgesic effects [134, 138, 139]. In contrast, mecamylamine did not affect tolerance to morphine’s analgesic effects [126].…”
Section: Ach As Treatment Target For Oud: Current Evidencementioning
confidence: 99%
“…First, sustained morphine incubation on primary cultured neurons precludes the involvement of glia cells in the development of tolerance regardless of the intimate interfaces or crosstalk between neurons and glia in this process (Chen et al, 2012b). Second, there is concern about chronic morphine-induced neurotoxicity and neuronal apoptosis both in vivo and in vitro (Mao et al, 2002b;Sharifipour et al, 2014;Svensson et al, 2008). Although the final concentration used in our study was the most commonly used dose in in vitro experiments, cultures derived from different tissues with different treatment paradigms or even during different developmental stages might respond differently to certain stimulants (Ma et al, 2001).…”
Section: Establishment Of Sustained Morphine Incubation Model In Vitromentioning
confidence: 99%
“…Cholinesterase inhibitors, currently used to treat Alzheimer's disease, including donepezil, rivastigmine, and galantamine, increase cholinergic activity and can be potential therapeutic targets in opioid abuse and dependence treatments [132]. Preclinical models have demonstrated that these cholinesterase inhibitors prevented morphine tolerance and attenuated the acquisition and expression of morphine CPP [133].…”
Section: Cholinergic Compoundsmentioning
confidence: 99%